2022
DOI: 10.1155/2022/9755129
|View full text |Cite
|
Sign up to set email alerts
|

Association between Baseline Cognitive Score and Postoperative Delirium in Parkinson’s Disease Patients following Deep Brain Stimulation Surgery

Abstract: Background. Deep brain stimulation of the subthalamic nuclei (STN-DBS) is a standard treatment option for advanced Parkinson’s disease (PD) patients. Delirium following DBS electrode implantation is common, by several studies, and cognitive impairment is a risk factor for developing postoperative delirium (POD). This prospective observational study was conducted to identify whether preoperative baseline cognitive status has an association with POD in PD patients undergoing DBS surgery. Methods. Preoperatively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(58 reference statements)
1
0
0
Order By: Relevance
“…**p < 0.01. (27)(28)(29), which is consistent with our results. Interestingly, the current study showed that patients with POD had lower lymphocytes, which can contribute to the proinflammatory response, which is a mechanism of POD (30).…”
Section: Discussionsupporting
confidence: 93%
“…**p < 0.01. (27)(28)(29), which is consistent with our results. Interestingly, the current study showed that patients with POD had lower lymphocytes, which can contribute to the proinflammatory response, which is a mechanism of POD (30).…”
Section: Discussionsupporting
confidence: 93%